Inkuiri Aksiologi Goa Janci sebagai Aset Budaya: Strategi Penciptaan Nilai Ekonomi Berbasis Warisan Budaya - Hasriady Hasriady; Muhammad Yamin; Sapda Mardalena; Riski Fadilah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Goa Janci is a local cultural asset with historical and cultural values, yet studies exploring the axiological values reflected in community experiences in treating it as a cultural asset remain limited. This study aims to analyze the axiological values reflected in community experiences and to explain the meaning of Goa Janci as a cultural asset from the community’s perspective through an inquiry approach. This research employs a descriptive qualitative method with data collected through observations, interviews, and relevant literature studies. The findings reveal that Goa Janci embodies axiological values including preservation, responsibility, mutual cooperation, education, cultural identity, and respect for ancestral heritage. Goa Janci is also interpreted as a source of local cultural learning, a symbol of community identity, and a medium for strengthening social relations. These findings highlight the importance of collaboration among communities, governments, and educational institutions in maintaining cultural values and developing cultural assets sustainably.